News Authorship and News Sources: Impacts on Environmental Coverage in The Nigerian Press - Emenyeonu, Ogadimma C.; Mohamad, Bahtiar (Jurnal The Messenger, 2017)
This study examines the impacts of news authorship and news sources on environmental coverage in the Nigerian press to shed light on the roles they play in news construction. The study finds that journalists in conjunction with policy makers are the catalyst for environmental information, whereas citizens who are pivotal in creating relevant public opinion on environmental issues are left behind. The study reveals that investigative reporting lacks in environmental coverage because most coverage are events driven which explains why environmental news is reported as straight news and as such journalists rely heavily on official sources rather than subsidiary sources. The study opines that for proper environmental coverage, journalists must choose sources from both main and subsidiary actors and revert to proactive, investigative and interpretive reporting so as to make environmental stories relatable to the intended audiences.